PENGEMBANGAN MEDIA PEMBELAJARAN APLIKASI BERBASIS ANDROID PADA MATA PELAJARAN DASAR-DASAR SENI RUPA - MEGGI MARIO, Drs. Suib Awrus, M. Pd., Drs. Abd. Hafiz, M.Pd. (Serupa The Journal of Art Education, 2018)
Research aims to produce android-based learning media in eyes of the fine Arts Basics in SMKN 4 Padang. Using the 4-D models is difintion, design, development and dissemination. The data questionnaire, validity, practicality, and effectiveness with current kappa with avarage results from expert media 0.88 and values of 0.86 material were very high validity. While the average value of the media practicality by the teacher was 0.86 and the efectiveness of the media by teachers and students was 0.89 with very high practicality categories. Concluded the learning media the basics of fine Art lesson is very valid and easy learning medium.Keyword : Pengembangan, media, android-based, 4-D model, SMKN 4 Padang